(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Social Networking has become a global phenomenon. Millions of people now use internet to engage on social networks. As in, there are more than 300 Social Networking Sites (SNS) and the total number of people using Social Networking Sites around the world is 1.73 billion according to 2013 Sensex. In few years, the usage of Social Networking Sites has surprisingly grown. These Social Networking Sites offers a wide variety of resources and services such as messaging, sharing of information, online marketing, blogging, connecting, sharing photos, audios, videos, group discussion, and distribution of applications. Consequently; especially youth, are the avid users of these sites. And, the usage of Social Networking Sites among the youth has increased rapidly throughout the world. Evidently, Social Networking Sites have become significant part of our lives. However, the study has been set forward to analyse the influence of Social Networking Sites on the interpersonal relationships of youth in Kerala state. Humans are social animals and Interpersonal Relationships are a very vital aspect of human existence. Hence, the impact of Social Networking Sites on interpersonal relationships needs to be examined through the lens of Sociology.